Ungoverned Spaces, Youths and Human Security Challenges: Interrogating Human Rights Based Development in the Niger Delta Region of Nigeria (JED (Jurnal Etika Demokrasi), 2024)
This study tries to examine the connection between the phenomenon of ‘ungoverned spaces’ and youths, and the challenges it poses to leadership in the Niger Delta region, South-south Nigeria.  The methodology applied by the study comprised the qualitative method, and two research designs, namely, Key Informant Interviews (KIIs) and Focus Groups.  Results of the study showed that lack of regulatory capability on the part of government, unemployment and poverty among youths, weakness of state security governance system, and the oil exploration and exploitation activities by the foreign multinational oil companies (MNOCs) contributed to the emergence and flourish of ungoverned spaces in the Niger Delta Region.  The study recommended the need for government to always ensure that it acquires enough regulatory capability. To achieve this, the study specifically recommended three measures.  The first measure was revitalization or stronger commitment to the deployment of the local government system and traditional institutions as a third-tier government and as a tool for grassroots governance.  The second measure was prioritization of the ‘bottom-up’ (rural-centric) approach to development policies and programmes as opposed to the ‘top-down’ (urban-centric) approach that tends to alienate or discriminate against territories located in the hinterlands.  The third measure was the need to strengthen the state security governance system through greater funding and equipping of the various law-enforcement and security agencies in the region.  Finally, the study also recommended urgent resolution of the protracted Niger Delta conflict, which is driven by struggle for resource control and political autonomy in the face of systemic poverty, unemployment, environmental pollution and degradation, economic injustice and lack of infrastructural and human capital development being inflicted by the MNOCs in concert with the Nigerian state and local bourgeoisie on the people of oil-bearing communities in the region.  Against this backdrop, the study also recommended a special form of development approach known as Human-Rights-based Development Approach, which is not only people-oriented and people-driven, but, as opposed to other forms of the development approach, has also all the essential elements of equity, justice, transparency, accountability, and participation and reflect the socio-cultural realities of the Niger Delta region.